Heartless - Showalter, Gena (Showalter, Gena. Immortal enemies., 2021)
After receiving a long-awaited heart transplant, a professional gamer girl begins to develop strange abilities and is soon launched into a mysterious world filled with fantastical and deadly creatures and ruled over by an extremely seductive man.